First record of Feltiella curtistylus Gagné (Diptera: Cecidomyiidae) in Argentina - Funes, Claudia Fernanda; Escobar, Lorena Inés; Palavecino, Braian Eduardo; Kirschbaum, Daniel Santiago (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
The first records of Feltiella curtistylus Gagné (Diptera: Cecidomyiidae) in Argentina are reported. Larvae from this species were captured in strawberry (Fragaria x ananassa Duch.) leaflets heavily infested with Tetranychus urticae Koch (Acari: Tetranichidae) in Famaillá, province of Tucumán, Argentina (27º03’S, 65º25’W). In 2015 (June, September and October), 16 larvae were collected; in 2016 (October, November and December), 23 larvae; and in 2017 (September, October and November), 49 larvae. Since F. curtistylus was found associated to a mite of agricultural importance in strawberry crops, this predatory gall midge has a potential for being considered a biological control agent. Highlights Feltiella curtistylus Gagné (Diptera: Cecidomyiidae) larvae are mite predators in Brazil and the USA. During 3 years, in Tucumán, Argentina, Diptera larvae were observed feeding on eggs, protonymphal and adult stages of two-spotted spider mite, in strawberry leaves heavily infested with. Leaflets with larvae were placed in Petri dishes with the bottom covered with smooth plaster base, and kept humid until adults emerged. Adult specimens (males and females) were identified by Dr. Raymond Gagné, as Feltiella curtistylus, first record for Argentina. Due to prey specificity, this predatory gall midge has a potential for been considered in augmentative biological control strategies in strawberry.